Aberrant DNA Methylation in Esophageal Squamous Cell Carcinoma: Biological and Clinical Implications - Lin, Lehang; Cheng, Xu; Yin, Dong (Frontiers in Oncology, 2020)
Almost all cancer cells possess multiple epigenetic abnormalities, which cooperate with genetic alterations to enable the acquisition of cancer hallmarks during tumorigenesis. As the most frequently found epigenetic change in human cancers, aberrant DNA methylation manifests at two major forms: global genomic DNA hypomethylation and locus-specific promoter region hypermethylation. It has been recognized as a critical contributor to esophageal squamous cell carcinoma (ESCC) malignant transformation. In ESCC, DNA methylation alterations affect genes involved in cell cycle regulation, DNA damage repair, and cancer-related signaling pathways. Aberrant DNA methylation patterns occur not only in ESCC tumors but also in precursor lesions. It adds another layer of complexity to the ESCC heterogeneity and may serve as early diagnostic, prognostic, and chemo-sensitive markers. Characterization of the DNA methylome in ESCC could help better understand its pathogenesis and develop improved therapies. We herein summarize the current research and knowledge about DNA methylation in ESCC and its clinical significance in diagnosis, prognosis, and treatment.